Identifikasi Miskonsepsi Mahasiswa pada Materi Asam Basa Menggunakan Four Tier Diagnostic Test (FTDT) - Priyasmika, Rendy; Ilmah, Mashfufatul (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2025)
Acid-base is one of the important chemistry materials and is a prerequisite knowledge for understanding subsequent chemistry materials. This material contains concrete, abstract concepts, and mathematical calculations so that it is considered difficult and has the potential to cause misconceptions. Therefore, a good and complete understanding of this concept is very important to avoid misconceptions that can hinder the learning process. The purpose of this study was to determine the types of misconceptions experienced by students in acid-base material. This study used a descriptive design with a quantitative approach. The subjects of the study were first-year students of Billfath University who took basic chemistry courses. The sampling technique used was saturated sampling. The data collection instrument developed and used was the four tiers diagnostic test (FTDT). The data analysis technique used was guided by the percentage of misconceptions in the sub-concepts and questions on acid-base material. The results showed that students experienced acid-base misconceptions in the moderate category with an average percentage of 31%. The highest misconceptions were identified in the sub-concept of the relationship between pH and water quality with a percentage of misconceptions of 45%. The lowest misconceptions were identified in the subconcepts of the Arrhenius and Bronstead-Lowry acid-base theories with a misconception percentage of 23%.